Pronunciation Errors in Reading Text Made By Students of English Language Education Department - Silalahi, Mardin; Sibuea, Bismar; Silalahi, Tiodora Fermiska; Purba, Anita (Journal of English Language and Education, 2025)
The objective of this research is to find out the pronunciation errors in reading text made by students of English Language Education department of Simalungun University. This research applied the qualitative approach with content analysis method. The technique of collecting data used a recording, and data analysis by transcribing the students’ pronunciation from recording into the phonetic transcriptions, grouping the students’ errors in pronouncing English vowels and consonants into separate divisions, employing the percentage descriptive analysis to count all errors, and interpreting the result of the data analysis. The result of research is found on English Vowels and English Consonants error. The pronunciation error on English vowel, namely: /i:/, /æ/, /ə/, /ɜ:/, /ɔ:/, and /u:/. The vowel pronunciation error is commonly on pure vowel. It is on a long vowel sound and short vowel sound. While the pronunciation error of English consonants found: /ʧ/, /ʤ/, /θ/, /ð/, /ʃ/, /ʒ/. The consonant pronunciation error appears on voiceless and voice consonants. The other consonant pronunciation error is to pronounce the double consonant. The students assumed that every double consonant would be pronounced with double sounds. The pronunciation error on English vowels and English consonants were caused some factors. Factors of pronunciation error, namely; 1. Lack of understanding and knowledge. 2. Students are nervous. 3. Students are unable to distinguish between sounds that are almost the same. 4. Students lack practice. 5. Native language. 6. Lack of new vocabulary. 7. Lack of confidence.